Why do we need interdisciplinary cooperation with anthropologists and archaeologists in soil science?. Issue 6 (25th October 2022) - Teuber, Sandra; Bartelheim, Martin; Hardenberg, Roland; Knopf, Monica; Knopf, Thomas; Kühn, Peter; Schade, Tobias; Schmidt, Karsten; Scholten, Thomas
Abstract: Looking at soils from the perspective of an environmental scientist or agronomist might neglect various dimensions of valuation that can be attributed to soils. Especially social and cultural connoted values including ecosystem services cannot always be measured in terms of scientific values or classified as soil types or soil qualities in a modern, economic way. Even though soils are a fact and have been present on the Earth's surface and used by people, at least for food production, at different times and in different cultures, the ways of dealing with soils and the valuations of soils are extremely diverse. Researchers in anthropology, archaeology, and agriculture, for example, are investigating different perspectives like soils as common good or as private property. This concerns not only different knowledge orders about soils, but also beliefs, techniques, foodways, practices, and power relations concerning soils and cereal cultivation. Based on the example of agriculture with a focus on cereal cultivation, we argue that there is still a great need for interdisciplinarity between the sciences and humanities. However, there is also a need to distinguish and explain between fundamental interdisciplinary research and application of findings in a socio‐economic context. It is necessary to understand different knowledge orders and valuations in time or space and to reevaluate today's perspectives on soils and agriculture for facing modern problems such as soil degradation, erosion, salinization, and an overall loss of soil fertility.